# Thread: Quadratic Equation

1. ## Quadratic Equation

Hi,

I don't think I'm getting the correct roots for this equation...

3x2(squared)- 2x- 6 = 0

That should read 3xsquared.

I had to use the b +/- formula and I'm getting x= 1.79 or x= -1.12

That can't be right???

2. Originally Posted by Larianne
Hi,

I don't think I'm getting the correct roots for this equation...

3x2(squared)- 2x- 6 = 0

That should read 3xsquared.

I had to use the b +/- formula and I'm getting x= 1.79 or x= -1.12

That can't be right???
$\displaystyle 3x^2 - 2x - 6 = 0$

Use the quadratic equation $\displaystyle -b+/- square root of \frac{b^2 -4ac}{2a}$

Where a is 3, b is -2 and c is -6.

3. Let's format that a little better: $\displaystyle x = \frac{b \pm \sqrt{b^2 - 4ac}}{2a}$

Why don't you think that's right? You rounded off to a few decimal places which will throw off your answer a little bit but it is correct (again, rounded of course)

4. Originally Posted by euclid2
$\displaystyle 3x^2 - 2x - 6 = 0$

Use the quadratic equation $\displaystyle -b+/- square root of \frac{b^2 -4ac}{2a}$

Where a is 3, b is -2 and c is -6.
Yes, I've done that but I put my answers back into the equation to check and I'm not getting zero.

5. Originally Posted by Larianne
Yes, I've done that but I put my answers back into the equation to check and I'm not getting zero.
$\displaystyle x = \frac{2 \pm \sqrt{-2^2 - 4(3)(-6)}}{2(3)}$
$\displaystyle x = \frac{2 \pm \sqrt{76}}{6}$
$\displaystyle x = \frac{2 + \sqrt{76}}{6}$ +
$\displaystyle x = \frac{2 - \sqrt{76}}{6}$
Therefore, $\displaystyle x =1.78 + x=-1.12$

6. Originally Posted by o_O
Let's format that a little better: $\displaystyle x = \frac{b \pm \sqrt{b^2 - 4ac}}{2a}$

Why don't you think that's right? You rounded off to a few decimal places which will throw off your answer a little bit but it is correct (again, rounded of course)
Should it not work out evenly???

7. Originally Posted by euclid2
$\displaystyle x = \frac{2 \pm \sqrt{-2^2 - 4(3)(-6)}}{2(3)}$
$\displaystyle x = \frac{2 \pm \sqrt{76}}{6}$
$\displaystyle x = \frac{2 + \sqrt{76}}{6}$ +
$\displaystyle x = \frac{2 - \sqrt{76}}{6}$
Therefore, $\displaystyle x =1.78 and x=-1.11$
So my answer is okay or should it be your answer???

8. Originally Posted by Larianne
So my answer is okay or should it be your answer???
Your answer is fine. Good job.